Gastrointestinal complications after pancreatoduodenectomy with epidural vs patient-controlled intravenous analgesia: a randomized clinical trial - Klotz, Rosa; Larmann, Jan; Klose, Christina; Bruckner, Thomas; Benner, Laura; Dörr-Harim, Colette; Tenckhoff, Solveig; Lock, Johan F.; Brede, Elmar-Marc; Salvia, Roberto; Polati, Enrico; Köninger, Jörg; et al. (JAMA surgery, 2020)
Importance Morbidity is still high in pancreatic surgery, driven mainly by gastrointestinal complications such as pancreatic fistula. Perioperative thoracic epidural analgesia (EDA) and patient-controlled intravenous analgesia (PCIA) are frequently used for pain control after pancreatic surgery. Evidence from a post hoc analysis suggests that PCIA is associated with fewer gastrointestinal complications. Objective To determine whether postoperative PCIA decreases the occurrence of gastrointestinal complications after pancreatic surgery compared with EDA. Design, Setting, and Participants In this adaptive, pragmatic, international, multicenter, superiority randomized clinical trial conducted from June 30, 2015, to October 1, 2017, 371 patients at 9 European pancreatic surgery centers who were scheduled for elective pancreatoduodenectomy were randomized to receive PCIA (n = 185) or EDA (n = 186); 248 patients (124 in each group) were analyzed. Data were analyzed from February 22 to April 25, 2019, using modified intention to treat and per protocol. Interventions Patients in the PCIA group received general anesthesia and postoperative PCIA with intravenous opioids with the help of a patient-controlled analgesia device. In the EDA group, patients received general anesthesia and intraoperative and postoperative EDA. Main Outcomes and Measures The primary end point was a composite of pancreatic fistula, bile leakage, delayed gastric emptying, gastrointestinal bleeding, or postoperative ileus within 30 days after surgery. Secondary end points included 30-day mortality, other complications, postoperative pain levels, intraoperative or postoperative use of vasopressor therapy, and fluid substitution. Results Among the 248 patients analyzed (147 men; mean [SD] age, 64.9 [10.7] years), the primary composite end point did not differ between the PCIA group (61 [49.2%]) and EDA group (57 [46.0%]) (odds ratio, 1.17; 95% CI, 0.71-1.95P = .54). Neither individual components of the primary end point nor 30-day mortality, postoperative pain levels, or intraoperative and postoperative substitution of fluids differed significantly between groups. Patients receiving EDA gained more weight by postoperative day 4 than patients receiving PCIA (mean [SD], 4.6 [3.8] vs 3.4 [3.6] kg;P = .03) and received more vasopressors (46 [37.1%] vs 31 [25.0%];P = .04). Failure of EDA occurred in 23 patients (18.5%). Conclusions and Relevance This study found that the choice between PCIA and EDA for pain control after pancreatic surgery should not be based on concerns regarding gastrointestinal complications because the 2 procedures are comparable with regard to effectiveness and safety. However, EDA was associated with several shortcomings. Trial Registration German Clinical Trials Register:DRKS00007784